2010
DOI: 10.1007/s10600-010-9643-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antioxidant activity of two Algerian Reseda species

Abstract: The Reseda genus is found in the Mediterranean and the Southwestern Asian areas [1]. In Algeria, there are twenty two species and subspecies [2,3]. Eight flavones [4][5][6][7][8][9], sixteen flavonols [7,8,[10][11][12][13][14][15][16], and one isoflavone [13] have been reported from the genus Reseda. R. villosa (Resedaceae) is an endemic species [1] collected from Ghardaia (Septentrional Algerian Sahara) in March 2002 and authenticated by Prof. Gerard De Belair (Annaba, Algeria). R. duriaeana (Resedaceae) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Moreover, they showed that Reseda extract was an interesting raw material dyeing purposes and for further pharmacologic investigation. In another study, Berrehal et al 38 investigated the methanolic and n-butanolic extracts of R. duriaeana and R. villosa for their antioxidant activity. The authors indicated that the methanolic and n-butanolic extracts of R. duriaeana exhibited better antioxidant activity than the respective extracts of R. villosa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they showed that Reseda extract was an interesting raw material dyeing purposes and for further pharmacologic investigation. In another study, Berrehal et al 38 investigated the methanolic and n-butanolic extracts of R. duriaeana and R. villosa for their antioxidant activity. The authors indicated that the methanolic and n-butanolic extracts of R. duriaeana exhibited better antioxidant activity than the respective extracts of R. villosa.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, different economically relevant autochthonous plants in Algeria ( Table S1 ) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], were chosen in their natural area in order to characterize their associated bacterial communities. In addition, the composition of the bacterial communities was also related to climatic variables and to the chemical and physical parameters of the soils.…”
Section: Introductionmentioning
confidence: 99%
“…Several of its species flourish on soils under arid environments, while others are ruderal weeds and only a few are available in high mountains [ 19 ]. Pharmacological studies of various Reseda species showed antimicrobial [ 20 ], anti-inflammatory [ 21 ], and antioxidant [ 22 ] activities. In Saudi Arabia, seven species of the genus Reseda were recorded, viz.…”
Section: Introductionmentioning
confidence: 99%